Effects of particle size, stem component and genotype on absorbency of kenaf (hibiscus cannabinus L.) grown in Nigeria for oil spill clean-up (2016)
The efficacies of different products made from different parts of the stem of different varieties of kenaf grown in Nigeria as oil absorbents were tested. Particle sizes, genotypes and whether mixed or sole stem core or bast differed among the treatments. The fibre component sank in water, and so was not buoyant; the core was partially buoyant while the mixed fibre and core was completely buoyant. Sorption capacity was the highest in the ground whole stem (8.16 g oil/g sorbent), which also retained (6.31 g oil/g sorbent) the highest quantity of oil. Sorption and retention of oil were the lowest in the fibre (1.66 and 0.69 g oil/g sorbent, respectively). After the first use, only the ground stem can be used to re-absorb up to 1.97 g oil/g sorbent of used sorbent. A mixture of genotypes was more absorbent than a single genotype. The implications of these findings in absorbency research are discussed.